2018
DOI: 10.1111/jfs.12597
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term application of CO2 gas: Effects on physicochemical, microbial, and sensory qualities of “Charlotte” strawberry during storage

Abstract: The effects of different concentrations (30, 50, and 70 kPa) and time (1 or 3 hr) of short‐term CO2 gas treatment on the quality, safety, and shelf life of “Charlotte” strawberry were evaluated during storage at 4°C. Color attributes were better maintained in CO2 treated strawberries while firmness increased significantly and maintained throughout the storage in 70 kPa CO2 treatments compared to untreated control. Total soluble solid, pH, and titratable acidity did not show remarkable changes among the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…A lower O2 and higher CO2 level can lead to an imbalance in tissue respiration, changes in anaerobic enzymes, accelerated tissue aging, weakened resilience, and a stimulation of bacterial growth [33]. Chandra et al [34] demonstrated that strawberries stored in 15-20% CO2 lower microbial counts toward the end of storage, in agreement with this experiment. CO2 is able to reduce inner microbial pH and withdraw phospholipid and hydrophilic complexes, thereby leading to microbial inactivation [35].…”
Section: Changes In Chlorophyll Contentsupporting
confidence: 68%
“…A lower O2 and higher CO2 level can lead to an imbalance in tissue respiration, changes in anaerobic enzymes, accelerated tissue aging, weakened resilience, and a stimulation of bacterial growth [33]. Chandra et al [34] demonstrated that strawberries stored in 15-20% CO2 lower microbial counts toward the end of storage, in agreement with this experiment. CO2 is able to reduce inner microbial pH and withdraw phospholipid and hydrophilic complexes, thereby leading to microbial inactivation [35].…”
Section: Changes In Chlorophyll Contentsupporting
confidence: 68%
“…The difference between the control groups and all elevated CO 2 treatments was pronounced, although no difference was found between elevated CO 2 pretreatments and Flow-CO 2 treatment in total phenolics but not in flavonoids. Although elevated CO 2 treatments slowed the loss of phenolic components, a decrease occurred after longer storage in all elevated CO 2 treatments and control groups which is similar to changes in strawberry [35].…”
Section: The Effect Of High Co 2 On Phenol Flavonoids and Dpph Of Green Asparagussupporting
confidence: 60%
“…Moreover, Chinese bayberry fruit mostly uses PP for semi-vacuum packaging. The gas concentration in the MAP package, especially the CO 2 concentration, has a major effect on preserving fruit freshness (Capotorto et al, 2020;Chandra et al, 2018). Therefore, it needs to test the concentration of headspace CO 2 gas.…”
Section: Gas Composition In the Package When Unpackingmentioning
confidence: 99%